Course of COVID-19 infection in patients with congenital adrenal hyperplasia - Javaid, Rida; Sinaii, Ninet; Kollender, Sarah; Desai, Jay; Moon, Amy; Merke, Deborah P. (Frontiers in Endocrinology, 2024)
Context: Patients with primary adrenal insufficiency due to congenital adrenal hyperplasia (CAH) are at risk for adrenal crisis during infectious illnesses. Increased risk of infection including COVID-19 has been variably reported.Objective: To evaluate COVID-19 illness outcomes and stress dose practices in a large cohort of patients with CAH during the first two years of the pandemic and compare observations of COVID-19 infection in patients with CAH to the general USA population.Methods: Between March 2020 and November 2022, patients with CAH followed at the National Institutes of Health Clinical Center were queried about COVID-19 infection during their routine visits. Cases of COVID-19 were compared to controls. COVID-19 infection rates and symptoms were compared to general USA population data from the Centers for Disease Control and Prevention.Results: Of 168 patient visits, there were 54 (32%) cases of COVID-19 infection, and 15 (28%) were pediatric. Overall an association was found between acquiring COVID-19 and obesity (p=0.018), and adults acquiring COVID-19 were on lower doses of fludrocortisone (p=0.008). Fewer cases of COVID-19 infection were reported in those receiving hydrocortisone or modified-release hydrocortisone compared to longer acting glucocorticoids (p=0.0018). In our CAH population, the pattern of COVID-19 infection rates and COVID-related symptomatology were similar to those observed in the general USA population. Most patients with the presumed alpha variant reported anosmia and ageusia, while gastrointestinal symptoms were commonly reported during the delta and omicron waves. Stress dosing occurred in 30/54 cases, and 7 received parenteral hydrocortisone. Two hospitalizations occurred; one pediatric and one adult, both with co-morbidities. There were 5 emergency room visits and no reported deaths.Patients with CAH with close follow-up do not appear to be at increased risk of acquiring COVID-19 or to have a more severe course of COVID-19 compared to the general USA population. Obesity may increase risk of acquiring COVID-19 in patients with CAH, and overall infection risk may be lower in those receiving short-acting and circadian glucocorticoid replacement therapy. Established age-appropriate guidelines for stress dosing during infectious illnesses should be used for patients with CAH and COVID-19. COVID-19 specific guidelines are not indicated.